Investigation of boron-doped graphene oxide anchored with copper sulphide flowers as visible light active photocatalyst for methylene blue degradation - Ahmad Farhan (17886734) (2023)
The non-biodegradable nature of waste emitted from the agriculture and industrial sector contaminates freshwater reserves. Fabrication of highly effective and low-cost heterogeneous photocatalysts is crucial for sustainable wastewater treatment. The present research study aims to construct a novel photocatalyst using a facile ultrasonication-assisted hydrothermal method. Metal sulphides and doped carbon support materials work well to fabricate hybrid sunlight active systems that efficiently harness green energy and are eco-friendly. Boron-doped graphene oxide-supported copper sulphide nanocomposite was synthesized hydrothermally and was assessed for sunlight-assisted photocatalytic degradation of methylene blue dye. BGO/CuS was characterized through various techniques such as SEM–EDS, XRD, XPS, FTIR, BET, PL, and UV–Vis DRS spectroscopy. The bandgap of BGO-CuS was found to be 2.51 eV as evaluated through the tauc plot method. The enhanced dye degradation was obtained at optimum conditions of pH = 8, catalyst concentration (20 mg/100 mL for BGO-CuS), oxidant dose (10 mM for BGO-CuS), and optimum time of irradiation was 60 min. The novel boron-doped nanocomposite effectively degraded methylene blue up to 95% under sunlight. Holes and hydroxyl radicals were the key reactive species. Response surface methodology was used to analyze the interaction among several interacting parameters to remove dye methylene blue effectively. Other Information Published in: Scientific Reports License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1038/s41598-023-36486-6